2001
DOI: 10.1208/pt020317
|View full text |Cite
|
Sign up to set email alerts
|

Porous bone morphogenetic protein-2 microspheres: Polymer binding and in vitro release

Abstract: This research compared the binding and release of recombinant human bone morphogenetic protein 2 (rhBMP-2) with a series of hydrophobic and hydrophilic poly-lactide-co-glycolide (PLGA) copolymers. Porous microspheres were produced via a double emulsion process. Binding and incorporation of protein were achieved by soaking microspheres in buffered protein solutions, filtering, and comparing protein concentration remaining to nonmicrosphere-containing samples. Protein release was determined by soaking bound micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Higher molecular weight polymers (RG503 and RG503H) yield a more viscous solution, which leads to bigger emulsion droplets and a relatively stable double emulsion, which corresponds to the increased size and more porous structure. Simultaneously, the uncapped polymer (RG503H) is more hydrophilic than the capped polymer, 20 which facilitates improved convection between the internal aqueous phase and the outer aqueous phase, which leads to the lower internal porosity and more pores on the surface. However, the less viscous solutions of lower molecular weight PLGAs reduce the stability of the double emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…Higher molecular weight polymers (RG503 and RG503H) yield a more viscous solution, which leads to bigger emulsion droplets and a relatively stable double emulsion, which corresponds to the increased size and more porous structure. Simultaneously, the uncapped polymer (RG503H) is more hydrophilic than the capped polymer, 20 which facilitates improved convection between the internal aqueous phase and the outer aqueous phase, which leads to the lower internal porosity and more pores on the surface. However, the less viscous solutions of lower molecular weight PLGAs reduce the stability of the double emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of studies have confirmed that rhBMP-2 released from gelatin alone or in combination with other ceramic scaffolds had a large initial burst release and resulted in imbalanced release of rhBMP-2. Recently, poly(lactic-co-glycolic acid) polymer has been commonly used for controlled delivery of rhBMP-2 and displayed a good release profile [35][36][37], but in general, the system was prepared with the growth factor incorporated within. This system may expose the protein to various organic solvents and temperature variations that may denature the growth factor completely or significantly reduce its bioactivity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted inverse relationships between “acid number” (a measure of carboxylic acid content of a polymer) and PLGA molecular weight or end-group chemistry. 30, 38 Here, we show that initial polymer chemistry also dictates evolution of bulk intraparticle pH during MP degradation (Fig 4A). Specifically, higher molecular weight (43 kDa) and ester-capped PLGA MPs have higher initial intraparticle pH and more gradual decreases in pH than lower molecular weight uncapped PLGA (Fig 4A).…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, these studies investigated the effects of polymer matrix charge density on “release”, rather than the influence of the amount of positive charge on the peptide or protein. 15, 30 …”
Section: Discussionmentioning
confidence: 99%